1999
DOI: 10.1375/twin.2.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Premature singleton versus a twin or triplet infant death: parental adjustment studied through a personal interview

Abstract: Par ental adjustment fol l ow i ng the death of a pr ematur e si ngl eton or mul ti pl e bi r th i nfant has hi ther to been studi ed by mai l ed questi onnai r es or tel ephone sur vey. I n the pr esent study, usi ng an i n-depth per sonal i nter vi ew, gr i ef r eacti ons and adjustment patter ns of ni ne families who lost a si ngl eton pr ematur e i nfant ('Si ngl e Gr oup') w er e compar ed w i th those of ni ne fami l i es w ho l ost one of a pr ematur e mul ti pl e bi r th cohor t ('M ul ti pl e Gr oup')… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Among other differences, these mothers suffered significant grief for longer periods than bereaved singleton mothers (Lang & Gottlieb, 1993;Potvin et al, 1989;Zeanah et al, 1995) and expressed more anxiety and depression. Similarly, earlier studies found that mothers and fathers of multiples did not experience significantly less grief compared with parents who had experienced the death of a singleton (Netzer & Arad, 1999;Wilson et al, 1982;Wilson et al, 1985).…”
Section: Grief and Consequences Of Bereavement For Parentsmentioning
confidence: 83%
See 3 more Smart Citations
“…Among other differences, these mothers suffered significant grief for longer periods than bereaved singleton mothers (Lang & Gottlieb, 1993;Potvin et al, 1989;Zeanah et al, 1995) and expressed more anxiety and depression. Similarly, earlier studies found that mothers and fathers of multiples did not experience significantly less grief compared with parents who had experienced the death of a singleton (Netzer & Arad, 1999;Wilson et al, 1982;Wilson et al, 1985).…”
Section: Grief and Consequences Of Bereavement For Parentsmentioning
confidence: 83%
“…The authors speculated that such a delay could reduce the potential for others to recognize the need for help and assist fathers (Wilson et al, 1985). All three studies found that over time the differences between mothers and fathers became less apparent and parental grief diminished (Netzer & Arad, 1999;Wilson et al, 1982;Wilson et al, 1985). However, Wilson et al (1985) found that mothers continued to report a greater need for social support than fathers.…”
Section: Grief and Consequences Of Bereavement For Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Previous studies of multiple-birth loss focused principally on grief. [14][15][16][17][18][19][20][21][22] The present study presents feedback from bereaved multiple-birth parents about life-support decisions and care surrounding their children's deaths.…”
Section: Introductionmentioning
confidence: 99%